A Novel Autosomal Recessive Nonsyndromic Hearing Impairment Locus (DFNB42) Maps to Chromosome 3q13.31-q22.3 - Aslam, Muhammad (2005)
A consanguineous family with autosomal recessive nonsyndromic hearing impairment (NSHI) was ascertained in Pakistan and displayed significant evidence of linkage to 3q13.31-q22.3. The novel locus (DFNB42) segregating in this kindred, maps to a 21.6 cM region according to a genetic map constructed using data from both the deCode and Marshfield genetic maps. This region of homozygosity is flanked by markers D3S1278 and D3S2453. A maximum multipoint LOD score of 3.72 was obtained at marker D3S4523. DFNB42 represents the third autosomal recessive NSHI locus to map to chromosome 3.